(untitled) (International Journal of Environmental Sciences, 2025)
The Protection of Women from Domestic Violence Act, 2005 (PWDVA) represents a significant legislative advancement in India, designed to protect women from various types of domestic violence—physical, emotional, verbal, sexual, and economic. Although the Act establishes a thorough legal framework for providing immediate assistance and long-term safety for victims, its application and success differ among states due to sociocultural, administrative, and infrastructural disparities. This overview analyzes the implementation and effectiveness of the PWDVA in the regions of Punjab and Haryana, which are recognized for their entrenched patriarchal values and unique legal and social obstacles. In both Punjab and Haryana, the recruitment and training of Protection Officers (POs), the involvement of the police and judiciary, and the accessibility of support services such as shelter homes and counselling facilities have been inconsistent. Haryana has achieved significant advancements by raising awareness through gender sensitization initiatives; however, rural and semi-urban regions continue to experience underreporting due to stigma, fear, and insufficient legal knowledge. Punjab, despite observing an increase in complaints filed under the Act, still grapples with delays in judicial processes and poor coordination among involved parties. To improve the efficacy of the PWDVA in Punjab and Haryana, it is crucial to secure additional funding for women’s support services, enhance training for Protection Officers, expedite case processing, and align the implementation of the PWDVA with other welfare initiatives. Furthermore, public awareness campaigns and community-based interventions can significantly contribute to challenging patriarchal norms and empowering women to pursue justice without apprehension. The PWDVA has provided empowerment to numerous women in Punjab and Haryana, systemic obstacles persist that impede its complete effectiveness. A comprehensive, multi-faceted strategy that includes legal reform, institutional enhancement, and shifts in societal attitudes is vital to ensure that the Act functions as a genuinely effective instrument for justice and protection.